Synthesis of β‐Substituted meso‐Tetraaryl‐21, 23‐dithiaporphyrins by Heck Reaction. Issue 27 (18th August 2015) - Forezi, Luana da S. M.; Gomes, Ana T. P. C.; Neves, Maria G. P. M. S.; Ferreira, Vitor F.; Boechat, Fernanda da C. S.; de Souza, Maria C. B. V.; Cavaleiro, José A. S.
Abstract: meso ‐Tetraphenyl‐21, 23‐dithiaporphyrin was selectively monobrominated at one β‐pyrrolic position in good yields. This dithiaporphyrin was then functionalized by Heck reaction with styrene derivatives containing different electronic features. The reaction profile was found to depend on the electronic characteristics of the styrene derivatives; the new compounds were fully characterized. Abstract : meso ‐Tetraphenyl‐21, 23‐dithiaporphyrin is selectively monobrominated at one β‐pyrrolic position in good yields. This dithiaporphyrin is then functionalized by Heck reaction with styrene derivatives containing different electronic features. The reaction profile is dependent on the electronic characteristics of the styrene derivatives; NBS = N ‐bromosuccinimide.